2019
DOI: 10.1017/neu.2019.30
|View full text |Cite
|
Sign up to set email alerts
|

The menstrual cycle may not be limited to the endometrium but also may impact gut permeability

Abstract: Objective:To examine associations between IgA responses to Gram-negative gut commensal bacteria and peri-menstrual symptoms and sex hormone levels during the menstrual cycle in women with and without premenstrual symptoms.Methods:Forty women aged 18–45 years completed the Daily Record of Severity of Problems (DRSP) during all 28 consecutive days of the menstrual cycle. We assayed, in plasma, IgA responses to six Gram-negative bacteria, that is, Hafnei alvei, Pseudomonas aeruginosa, Morganella morganii, Klebsie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 85 publications
(101 reference statements)
0
17
0
Order By: Relevance
“…Fasting blood was sampled at 8.00 a.m. to assay plasma oestradiol and progesterone using an immunoassay for the quantitative determination of oestradiol and progesterone using Cobas ® 601. The methods to measure both sex hormones are described at great length in our previous published work (Roomruangwong et al, 2019a, b). The intra-assay CV value is 1.2% for oestradiol and 2.3% for progesterone.…”
Section: Methodsmentioning
confidence: 99%
“…Fasting blood was sampled at 8.00 a.m. to assay plasma oestradiol and progesterone using an immunoassay for the quantitative determination of oestradiol and progesterone using Cobas ® 601. The methods to measure both sex hormones are described at great length in our previous published work (Roomruangwong et al, 2019a, b). The intra-assay CV value is 1.2% for oestradiol and 2.3% for progesterone.…”
Section: Methodsmentioning
confidence: 99%
“…morganii and Pseudomonas putida were significantly associated with changes in the total DRSP scores and 2 subdomains namely "physio-somatic" and "breast-craving". H. alvei was also detected to be associated with "anxiety" subdomain 13 . Lastly, we also found that changes in the DRSP score were significantly associated with changes in PON1 activity, MDA and C4…”
Section: Biomarkers Validation Of the Pms Case Definitionsmentioning
confidence: 94%
“…We again observed significant associations between MCAS, but not ACOG, PMS and PeriMS, case definitions and lowered PON1 activity, increased LOOH and C4 levels(Roomruangwong et al, submitted). Nevertheless, in another biomarker study on IgA mediated immune responses to LPS of Gram-negative bacteria, there were no significant associations between the changes in the IgA responses to LPS and any of the 4 case definitions although changes in these biomarkers during the menstrual cycle were highly significantly correlated with changes in the DRSP score13 .Biomarker validation of the total DRSP score and its 4 subdomainsApart from externally validating different case definitions, it is also important to examine the changes in DRSP scores (total and subdomains) all over the menstrual cycle in association with changes in the biomarkers, and the mean DRSP score averaged over all time points in association with steady-state biomarker levels which are averaged over the menstrual cycle. Using repeated measurement design analyses, we found that the time series of the DRSP score was significantly and incersely associated with the time series in both progesterone and oestradiol levels and additionally with the steady state levels in progesterone.…”
mentioning
confidence: 90%
“…We used the PARA+VASC/TRANS score [28] as an index of breakdown of paracellular and vascular pathway, computed as z (z score of IgA to occludin (z Occludin) + z Claudin-5 + z E-cadherin + z β-catenin + z PLVAP) -z score (z talin + z actin + z vinculin + z EIF). As explained previously, IgA and IgM isotypes directed to the LPS of Hafnia alvei, Klebsiella pneumonia, Morganella morganii, Pseudomonas aeruginosa, and Pseudomonas putida were assayed using ELISA methods [37]. Consequently, we computed the sum of all 5 IgA and all 5 IgM responses to those bacteria as indicants of bacteria load (BACT-LOAD).…”
Section: Assaysmentioning
confidence: 99%